Monitoring Keamanan Rumah Terhadap Bahaya Kebakaran Dan Untuk Efisiensi Biaya Berbasis SMS Gateway - Anshory, Izza; Charizuddin, Muhammad (Universitas Hang Tuah, 2019)
Atthidtimea lotof automationis used invariousfields that are mandatory tokmakeiteasierfor human todo allthe work. This researchisintendedtocreate a monitoring system. Thissecurity system uses arduino microcontroller asthe main controllerthatservesto improve thesignalfromthelight sensor, flame sensor,andgassensor which isthen used asoutputsignal andsenttotheactuator.Device that actas inputonthissystemare3types of sensors,theLDRsensor asa light input,flamesensoras firedetector input,andMQ-2 gassensor that servesasagasleak detector. The programon the arduino isenabled to configure andinitialize the hardware andreceive inputsignalsfromthe 3 sensorswhichwillthebe processed undersomeconditionsto producethe desired output. MQ-2 and LDR sensor test resultshowdata witha fairly good standard deviation and thisfinalresultisa homesecurity system that is monitored through SMSGateway withfastspeed notificationdelivery speedusing Telkomsel Provider.